Anti-Dislipidemia Effectiveness Test of Turmeric Ethanol Extract (Curcuma Longa) in Male Wistar Mice Given Propylthiouracil (PTU) - Ke Huajing; Florenly Florenly; Johannes Bastira Ginting; Fioni Fioni (Budapest International Research and Critics University, 2022)
Dyslipidemia is a lipid metabolic disorder that is a risk factor for coronary heart disease (CHD). According to the American Heart Association, data from 2013 to 2016, as many as 92.8 million adults in America have total cholesterol of more than 200 mg / dL. Curcumin, the main compound in turmeric, can lower cholesterol levels due to inhibiting the reabsorption of cholesterol derived from the outside (exogenous) and increasing the enzyme HMG-CoA reductase inhibitor so that fat synthesis can run well. The purpose of this study was to find out the effectiveness of mangosteen peel ethanol extract as an anti-dyslipidemia in male Wistar rats given Propylthiouracil (PTU). This study is an experimental study with a Pre-test and Post-test group only control design approach that uses male Wistar rats as test animals and turmeric extract. The study was conducted in March 2021, at the Herbarium Medanese FMIPA USU, the Pharmacognosy Laboratory of the FACULTY of Pharmacy USU, and the Laboratory of Pharmaceutical Pharmacology USU. Descriptive data analysis (Central tendency and Dyspersi) in the form of lipid profiles (LDL, HDL, Total Cholesterol, and Triglycerides), color, texture, weights. Then analyzed with One-Way Anova if the distributed data is normal, if the distributed data is not normal, then the Kruskal-Wallis test is used. The results and conclusions, turmeric ethanol extract (Curcuma Longa) III (151.70 ± 0.95 mg/dl) can significantly decrease total cholesterol compared to the control group (178.50 ± 6.05mg/dl) (P-value < 0.05). Turmeric ethanol extract (Curcuma Longa) III (110.00 ± (109-112) mg/dl) may significantly lower triglyceride levels compared to the control group (167.00 (162-179) mg/dl). (Value P = 0.027). Turmeric ethanol extract (Curcuma Longa) III (68.50 ± 1.28 mg/dl) significantly lowered LDL levels compared to the control group (107.20 ± 3.60 mg/dl). (P-value < 0.05). Turmeric ethanol extract (Curcuma Longa) III, (61.00 (60-62) mg/dl) may significantly increase HDL levels compared to the control group (28.50 (37-45) mg/dl). (Value P = 0.027). Turmeric ethanol extract (Curcuma Longa) III significantly lowered SGOT (Value = 0.027) and SGPT (Value P < 0.05) compared to the control group.